Collaborative Writing Learning in Inquiry to Improve Critical Thinking Skills - Shofiah, Nurul; Putera, Zulmy Faqihuddin; Widiastuti, Sripit (Journal of English for Academic and Specific Purposes (JEASP), 2024)
In tertiary education, the enhancement of writing skills is paramount. One effective approach to mastering academic writing is through inquiry-based collaborative learning. Hence, this study endeavors to delineate the procedures involved and gauge students' perceptions of inquiry-based collaborative writing in enhancing critical thinking skills within the Indonesian language curriculum. This research adopts a descriptive methodology, employing research instruments such as observation sheets and surveys to gather data. The findings elucidate two key points: firstly, the inquiry-based collaborative writing process comprises five integral stages - orientation, collaboration, investigation, discussion, and conclusion. Secondly, student feedback highlights the positive impact of this method in nurturing critical thinking skills specifically within the realm of Indonesian language studies. Given its fusion of activity-oriented learning, logical argumentation, and collaborative dynamics, inquiry-based collaborative writing emerges as a potent tool for cultivating critical thinking skills among students. Consequently, its incorporation into the curriculum is recommended as a strategic means to bolster students' cognitive abilities and academic proficiency